Perception, hallucination, virtual reality. From controlled hallucination to Resident Evil 7: Biohazard (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2022)
In this paper, I will work on the relationship between perception and imagination in Virtual Reality, claiming that “hallucination” is the ordinary motor also for online perception and not only a deviant form of it. First, I will deal with the problem of perception from the point of view of cognitive semiotics and I will try to underline the crucial role of imagination, claiming that perception is a form of “controlled hallucination”. Later, I will focus on the relationship between perception, hallucination, and memory in Virtual Reality. On the one hand, I will claim that Virtual Reality expresses the transition from actual perception to imagination, memory or dream through another actual perception. On the other hand, I will claim that it can express it without any problems through the old techniques coming from cinema and other audiovisual languages, since they partially share the very same formal apparatus of enunciation. I will demonstrate all of this by analyzing Resident Evil 7: Biohazard.
Keywords: Perception; Imagination; Hallucination; Enunciation; Resident Evil